Analysis of chemical product sales based on product classification and customer profitability using the ABC analysis method - Muhammad Haikal; Fransisca Debora Debora (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Managing product and customer portfolios is a significant challenge in the chemical distribution industry because sales contributions are not evenly distributed across all items and customers. This study aims to analyze product and customer sales contributions based on sales value using the ABC classification method at PT Era Specialty Chemical. The analysis was conducted using the Pareto principle through separate classifications of products and customers, where category A represents approximately 70–80% of the cumulative sales contribution, category B 15–25%, and category C 5–10%. The data used are annual sales data for five main paint raw materials and transaction data from 37 active customers over a one-year period. The results show a concentrated sales structure, with Pigment Yellow 14 contributing 44% of total sales, thus becoming the main determinant of the company's revenue performance. In terms of customers, two category A customers, namely PT Intimas Wisesa and PT Hi-Tech Ink Indonesia, cumulatively contribute more than 62% to total sales, indicating a dependence on a small number of key customers. The product–customer matrix mapping shows that superior products are dominated by priority customers while revealing cross-selling opportunities and potential risks of dependence on certain combinations. These findings confirm that the company's sales structure follows a Pareto pattern, where a small number of products and customers generate the majority of revenue. Practically, the research results provide a quantitative basis for prioritizing product management, customer relationship strategies, and optimizing sales portfolios, while also strengthening the role of ABC analysis as a data-driven decision-support tool in distribution management.